The current use, and opinions of elite athletes and support staff in relation to genetic testing in elite sport within the UK - Varley, I.; Patel, S.; Williams, A. G.; Hennis, P. J. (Biology of Sport, 2018)
The purpose of the study was to investigate the current use of genetic testing in UK elite sport and assess how genetic testing might be received by those employed in elite sport. Seventy-two elite athletes and 95 support staff at UK sports clubs and governing bodies completed an online survey of 11 questions concerning their experience of genetic testing and beliefs regarding the use of genetic testing in sport. Genetic testing related to sports performance and injury susceptibility is conducted in UK elite sport, albeit by a relatively small proportion of athletes (.17%) and support staff (.8%). Athletes and their support staff agree that genetics are important in determining elite status (.79%) and appear willing to engage in genetic testing for individualising training to improve sport performance and reduce injury risk. Opinion was divided on whether genetic information should be used to identify talented athletes and influence selection, eligibility or employment status. Genetic testing for sports performance and injury susceptibility occurs in UK elite sport, however it is not commonly conducted. There is a belief that genetics is an important factor in determining an athlete and there is a willingness to engage in genetic testing for sports performance and injury susceptibility.